The impact of self-regulation of students’ educational activity on success in learning process - Khamzina, B.E.; Kostangeldinova, A.A.; Konurova-Idrissova, Z.K.; Kudussov, A.S.; Akhmetova, T.B.; Konyrbayeva, A.K. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
In this article the authors investigate the problem of self-regulation of students as a factor influencing on success in leaning process. The work shows the theoretical part of the research: hypothesis, goal, objectives, methods, scientific novelty and significance stages, methodological and theoretical basis of the research. In this work the authors presents possibilities, methods and means of the development of self-regulation of pupils and the impact of self-regulation of students’ educational activity on success in learning process. In research they studied and considered three components of self-regulation: self-control in educational work, social self-control and ability to strong-willed efforts in intellectual work as self-regulation means. The results of pedagogical experiment are presented in the following publication.
Оқушылардың оқу іс-əрекетіндегі үлгеріміне өзін-өзі реттеудің ықпалы туралы
О влиянии саморегуляции учебной деятельности студентов на успешность их обучения
Keywords: student; self-regulation; self-control; self-estimation; reflection; self-correction